2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20185513
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of various cutaneous manifestations in neonates

Abstract: <p class="abstract"><strong>Background:</strong> Cutaneous manifestations are common in neonates. Transient and pathological neonatal dermatoses should be differentiated to avoid unnecessary treatment and thus considering the variable nature and severity of neonatal skin lesions, it is important to be aware of the transient skin lesions in newborn and to differentiate these from other serious conditions which will avoid unnecessary therapy to the neonates and the parents can be assured of goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…In comparison to the former conducted studies, the maximum number of neonates found were >2.5 kg weight at birth. [ 11 , 12 , 15 ] The present study's findings regarding neonatal birth weight are in accordance with the findings observed in different studies. The birth weight of a newborn depends on genetic, environmental, parental socioeconomic status, maternal nutrition, and other maternal factors.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In comparison to the former conducted studies, the maximum number of neonates found were >2.5 kg weight at birth. [ 11 , 12 , 15 ] The present study's findings regarding neonatal birth weight are in accordance with the findings observed in different studies. The birth weight of a newborn depends on genetic, environmental, parental socioeconomic status, maternal nutrition, and other maternal factors.…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies concluded a prevalence of ND of 519 (90.7%) 474 (94.8%), 132 (74.6%), and 577 (34.75%), respectively. [ 8 , 9 , 10 , 11 ] The frequency of ND mentioned in the current study is approximately identical to the above-mentioned studies. Numerous reviews of the frequency of ND have been registered in several nations and with different ethnicities.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations